Socio-Economic Status of Rural Dwellers and the Accessibility of Primary Healthcare Facilities on Child Health Management in Kurmi LGA of Taraba State, Nigeria - O, Nwanma Gloria; Asabe, Ibrahim; Ojoma, Ako (Darul Yasin Al Sys, 2025)
Poverty, as a pervasive socio-economic factor, significantly shapes child health in rural settings. Insufficient financial resources contribute to inadequate nutrition, limited access to healthcare, and substandard living conditions. Research consistently indicates that children from impoverished backgrounds face increased risks of health challenges, including malnutrition, higher rates of infectious diseases, and developmental delays. Parental education levels play a pivotal role in child health management. Low educational attainment is often linked to reduced health literacy, hindering parents' ability to make informed decisions about their child's well-being. Objective of the study is to ascertain how socio-economic status of rural dwellers influence their accessibility to primary healthcare facilities on child health management in Kurmi LGA of Taraba State. A cross sectional survey design was adopted with Taro Yamane’s formula which help the researchers in generating the sample size of the study. The study’s findings revealed that income levels, educational levels, cost of primary healthcare facilities, occupational level, and the distance to primary healthcare facilities were responsible for the accessibility of primary healthcare facilities on child’s health management among rural dwellers in Kurmi LGA of Taraba State. This implied that there were significant relationships between the socio-economic variables and accessibility of primary healthcare facilities on child health management among the rural dwellers. The study recommended that more community health workers and traditional birth attendants should be trained to provide basic health care services in rural areas, and incentives such as financial or in-kind benefits should be provided for health workers who work in rural areas.